A Dictionary of Middle English Musical Terms - Carter, Henry (Indiana University Press, 1961)
The work here presented is a definitive study of Middle English musical terms, arranged on a modified historical principle and based, as the bibliography will show, on essentially everything published in Middle English. Terms included in the study refer to the theory, the performance, the materials, and the forms of Middle English music. As in the OED and MED, but with more concentration on musical applications, definitions are given for all terms and are illustrated by chronologically arranged examples. For terms of low incidence all of Professor Carter's quotations have been used; for those of moderate or high incidence, only the earliest, and the most varied and interesting.